The effect of human resource management (HRM) practices in service-oriented organizational citizenship behaviour (OCB): Case of telecommunications and internet service providers in Malaysia - Thanigaivel R, Krishnan *; Liew, Su Ann*; Koon, Vui Yee* (Canadian Center of Science and Education, 2017)
In the human resource management-organizational performance research context, this paper is focusing on the effect of Human Resource Management (HRM) practices (pay practice, job security, training and development, supervisor support) on service-oriented Organizational Citizenship Behaviour (OCB) in Malaysian telecommunication and internet service providers. A quantitative study was conducted on 204 customer-contact employees who working in telecommunications and internet service providers in Malaysia. Correlation analysis and multiple regression analysis were applied to analyse the relationships between HRM practices and service-oriented OCB. The results indicate that, job security, training and development, supervisor support and overall perceptions of HRM practices have positive and significant effect on service-oriented OCB with the exception for pay practice.